Effect of basalt aggregates and plasticizer on the compressive strength of concrete - Al-Rawashdeh, Mohammad; Shaqadan, Ashraf (International Journal of Engineering and Technology, 2015)
The purpose of this research is to investigate the feasibility of using basalt aggregates and plasticizers in concrete mixes. An elaborate experimental program that included a variation of plasticizer and basalt in concrete mixes. The laboratory investigation included measurements of sieve analysis, compressive strength, and slump test. The compressive test was evaluated at 7, 14, 28 days of curing time. The results show significant improvement in concrete strength up to 2% of additive plasticizer after that concrete strength was reduced.